Anthropometric Changes in Female Participants Enrolled in a Combined Aerobic and Resistance Training Program for Longer than 1 Year: A Cohort Study - Jung-Sun Lim; Hee-Jin Hwang; Yoon Hee Eum; Ho Jun Kim; Booyoon Cheung; Han Jin Oh; Bumjo Oh (Journal of Obesity & Metabolic Syndrome)
Background : To analyze the anthropometric changes in women who had participated in a combined resistance and aerobic training program for more than a year and to determine the effect of the exercise on weight loss. Methods : A total of 9,128 women aged between 20 and 60 years who registered in the Curves program, which employs a combination of resistance and aerobic training exercises, and who participated for more than 1 year were included in our analysis. The women were divided into groups according to exercise frequency: <1, 1, 2, and ≥3 days/week. Weight and waist circumference were measured at the beginning and end of the follow-up period. Results : The average follow-up duration was 625.3±151.2 days. Waist circumference and body weight decreased more on average in those who participated more frequently in exercise. The achievement of more than 5% weight reduction became more likely with increasing frequency of exercise participation. The odds ratios of more than 5% weight reduction between the exercise groups were 1.47, 1.58, and 2.05 for the 1, 2, and ≥3 days/week exercise groups, respectively. Conclusion : Women who participated in a combined resistance and aerobic training program for more than a year lost weight in a dose-dependent manner.